(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The initial drought, plants develop a memory that results in partial stomatal opening during the watered recovery interval, increased levels of osmoprotectants and abscisic acid (ABA), and a dampened photosynthesis response during the subsequent drought. This short-term memory is regulated by ABA and other phytohormones, with transcriptional memory observed in various genes through the deposition of methylated histones at drought-tolerance genes. RNA polymerase activity is stalled during the recovery interval, ready to be activated promptly in the subsequent drought by a pause-breaking factor. Drought stress also induces DNA demethylation near drought-response genes, indicating a genetic control of the process. Progenies of drought-exposed plants inherit specific methylation patterns, which enhances their adaptation to drought conditions. However, an extended watered recovery interval can lead to the loss of drought memory, facilitated by certain demethylases and chromatin accessibility factors. Small RNAs play a crucial role in regulating drought memory by modulating transcript levels of drought-responsive target genes. Future research is expected to delve further into the genetic regulation of drought memory and explore the interplay between genetic and epigenetic factors in its inheritance. Studying plants from extreme environments can provide valuable insights into robust memory responses at the ecosystem level.